Combining new tools to assess renal function and morphology: a holistic approach to study the effects of aging and a congenital nephron deficit - Geraci, Stefania; Chacón-Caldera, Jorge; Schad, Lothar R.; Sticht, Carsten; Gretz, Norbert (American journal of physiology. Renal physiology, 2017)
Recently, new methods for assessing renal function in conscious mice (transcutaneous assessment) and for counting and sizing all glomeruli in whole kidneys (MRI) have been described. In the present study, these methods were used to assess renal structure and function in aging mice, and in mice born with a congenital low-nephron endowment. Age-related nephron loss was analyzed in adult C57BL/6 mice (10-50 wk of age), and congenital nephron deficit was assessed in glial cell line-derived neurotrophic factor heterozygous (GDNF HET)-null mutant mice. Renal function was measured through the transcutaneous quantitation of fluorescein isothiocyanate-sinistrin half-life (t1/2) in conscious mice. MRI was used to image, count, and size cationic-ferritin labeled glomeruli in whole kidneys ex vivo. Design-based stereology was used to validate the MRI measurements of glomerular number and mean volume. In adult C57BL/6 mice, older age was associated with fewer and larger glomeruli, and a rightward shift in the glomerular size distribution. These changes coincided with a decrease in renal function. GNDF HET mice had a congenital nephron deficit that was associated with glomerular hypertrophy and exacerbated by aging. These findings suggest that glomerular hypertrophy and hyperfiltration are compensatory processes that can occur in conjunction with both age-related nephron loss and congenital nephron deficiency. The combination of measurement of renal function in conscious animals and quantitation of glomerular number, volume, and volume distribution provides a powerful new tool for investigating aspects of renal aging and functional changes.